(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of cardiomyopathy in beta thalassemic children. Study Design: Cross-sectional descriptive study Place and Duration of Study: This study was carried out in the Pediatric department of Postgraduate Medical institute Lady Reading Hospital Peshawar from 1.1.2013 to 31.12.2013. Materials and Methods: Total 334 Cases were collected by Consecutive (non probability) sampling technique using WHO sample size calculation soft ware. Patients collected according to fulfilling the inclusion/exclusion criteria. Beta thalassemic children with 10 or more blood transfusions, aged 2 to 15 years and both male and female children. Results: In this study, 334 patients suffering from beta thalassemia were included. Male to female ratio was 1.62:1 and age ranged from 2 to 15 years. Average age was 7.57 years + 3.79SD. Dilated cardiomyopathy in beta thalassemic was observed in 13(3.9%), while restrictive cardiomyopathy was in 9(2.7%)patients. Conclusion: The majority of patients with beta-thalassaemia demonstrated a unique hemodynamic pattern indicating cardiomyopathy.